Perancangan dan Pembuatan Aplikasi Penjualan Toko Sepatu “Alcin” Menggunakan Visual Studio - Arby, Aisyah Lintang Zakiyya; Ayuni, Cintya Ratna; Basatha, Rizky (Al-DYAS, 2025)
This research aims to develop a shoe sales application at Alcin Shoe Shop using visual studio. This application is designed to be able to improve management efficiency, speed up transactions, and generate automatic sales reports. The research method used is qualitative with a case study approach. Data is collected through interviews, observations, and document analysis. The results of the study show that the developed application successfully overcomes operational management problems and increases customer satisfaction. In conclusion, this application is an effective solution to increase the competitiveness of shoe stores in the digital era.